ATP1A3 spectrum disorders: A video-documented history of 7 genetically confirmed early onset cases. (March 2018) - Stagnaro, Michela; Pisciotta, Livia; Gherzi, Marcella; Di Rocco, Maja; Gurrieri, Fiorella; Parrini, Elena; Prato, Giulia; Veneselli, Edvige; De Grandis, Elisa
Abstract: Mutations in the ATP1A3 gene, which encodes the alpha3 -subunit of sodium-potassium ATPase, are related to a spectrum of neurological diseases including Rapid onset Dystonia-Parkinsonism (RDP), Alternating Hemiplegia of Childhood (AHC) and Cerebellar ataxia, Areflexia, Pes cavus, Optic atrophy and Sensorineural hearing loss (CAPOS) syndrome. Moreover, an increasing number of patients with intermediate and non classical phenotypes have been reported. Herein we describe 7 patients with 6 different de novo ATP1A3 mutations, and we focus on paroxysmal and chronic movement disorders with the help of video documentation. Our cases confirm that ATP1A3 -related neurological disorders make up a phenotypic continuum rather than overlapping syndromes, in which early onset dystonia, ataxia and paroxysmal episodes with triggering or worsening factors are key diagnostic clues. Moreover, our experience suggests that ATP1A3 gene analysis should be extended both to children with channelopathy-like spells and to patients with early onset, fever-related encephalopathy. Highlights: ATP1A3 disorders include an expanding genotypic and phenotypic spectrum. We present 7 early onset ATP1A3 cases with video documentation. Channelopathy-like spells and fever-related encephalopathy may be related to ATP1A3 .